Women at heart: Introducing gender cardio-oncology - Canale, Maria Laura; Bisceglia, Irma; Gallucci, Giuseppina; Russo, Giulia; Camerini, Andrea; Di Fusco, Stefania Angela; Paccone, Andrea; Camilli, Massimiliano; Fiscella, Damiana; Lestuzzi, Chiara; Turazza, Fabio Maria; Gulizia, Michele Massimo; et al. (Frontiers in Cardiovascular Medicine, 2022)
As cardio-oncology imposed as the reference specialty for a comprehensive cardiovascular approach to all cancer patients, a more specific and careful cardiac evaluation of women entering their journey into cancer care is needed. Gender medicine refers to the study of how sex-based biological and gender-based socioeconomic and cultural differences influence people’s health. Gender-related aspects could account for differences in the development, progression and clinical signs of diseases as well as in treatment adverse events. Gender also accounts for major differences in access to healthcare. As for medicine and health-care in general, gender-related characteristics have gained significance in cardio-oncology and should no longer be neglected in both clinical practice and research. We aimed to review the most relevant cardiovascular issues in women related to cardio-oncology approach to offer a specific gender-related point-of-view for clinicians involved in the care process for both cancer and cardiovascular disease.